Efeitos fisiológicos do mercúrio em plantas de Pfaffia glomerata (Spreng.) Pedersen - Calgaroto, Niceia Spanholi (2009)
Mercury (Hg) is a highly toxic non-essential heavy metal. Soil, water and air contamination by Hg leads to its accumulation in fish, birds and mammals, thus entering human food. Due to the hazardous effects to the ecosystem, it is necessary that contaminated soils be rehabilitated. Phytoremediation is a cheap technique that can be utilizated with this objective, however, it is necessary to be knowledgeable about plant behavior during metal exposure. Therefore, the aim of this study was to characterize biological and biochemical aspects of Hg toxicity and the role of Zn to alleviate these effects in P. glomerata plants. For both experiments, plants were grown in vitro and acclimated ex vitro, for the application of treatments. Nine days later, growth and biochemical parameters of oxidative stress were evaluated. In the first experiment, plants were exposed to four concentrations (0.0, 1.0, 25 and 50 μM Hg). In the second experiment, four treatments of Hg and Zn were added to the nutrient solution (without Zn or Hg (control); 50 μM Zn; 50 μM Hg and; 50 μM Zn + 50 μM Hg). The Hg concentration was higher in shoot than in roots only in treatments without Hg (control and 50 μM Zn). Fresh and dry weight of roots and shoot decreased and a high malondialdeide (MDA) concentration was observed at 50 μM Hg, indicating that tissue damage occurred. The antioxidant enzyme activity and non-enzymatic concentration increased with the presence of Zn+Hg. Plants exposed to Zn showed a decrease in fresh and dry weight, but there was no significant increase in MDA production. There was an interaction between Zn and Hg. The antioxidant system of P. glomerata plants was important in oxidative damage regulation, however, at 50 μM Hg these mechanisms were not able to revert the damage caused by Hg. Zinc addition parcially prevented Hg damage, observed by the significant decrease in lipid peroxidation and higher survival percentage.